2016
DOI: 10.1002/ep.12489
|View full text |Cite
|
Sign up to set email alerts
|

Furfural production from corncobs using thiourea as additive

Abstract: Furfural production from the conversion of corncob was investigated using sulfuric acid as catalyst and thiourea as additive. The effects of acid concentration, temperature and thiourea on furfural yield were investigated. A furfural yield of 61.04% is achieved using thiourea as additive compared with 33.78% using H2SO4 alone without additive, under the optimum conditions of liquid–solid ratio of 2:1, temperature of 170°C and sulfuric acid of 0.5M. The effect of thiourea on furfural degradation rate was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…After optimizing the conditions and catalyst concentrations (170 °C, 90 min, in water), 34% yield was obtained without thiourea. However, when 16 mM thiourea was added, the yield increased to 61% . Without any additive, a similar result (37%) was reported for corncob conversion in hydrochloric acid .…”
Section: Synthesis Of Platform Chemicalssupporting
confidence: 82%
See 1 more Smart Citation
“…After optimizing the conditions and catalyst concentrations (170 °C, 90 min, in water), 34% yield was obtained without thiourea. However, when 16 mM thiourea was added, the yield increased to 61% . Without any additive, a similar result (37%) was reported for corncob conversion in hydrochloric acid .…”
Section: Synthesis Of Platform Chemicalssupporting
confidence: 82%
“…However, when 16 mM thiourea was added, the yield increased to 61%. 287 Without any additive, a similar result (37%) was reported for corncob conversion in hydrochloric acid. 288 Formic acid appears as coproduct during the conversion of C 6 -fraction of biomass.…”
Section: Processing Of Succinic Acid (Downstream)supporting
confidence: 73%
“…Different additives such as thiourea, NaHSO 4 , NaCl were also tested as potential improvers of the dehydration process. For example, the impact of thiourea additive in the furfural production process from corncobs treatment using H 2 SO 4 was described (Xu et al, 2017 ). They reported that thiourea had for effect to improve the furfural yield that reached 61% under a liquid-solid ratio of 2:1 instead 34% with only H 2 SO 4 .…”
Section: Synthesis Of Furfural From Sugars and Polysaccharides Using mentioning
confidence: 99%
“…Thiocyanate is a negatively charged polyatomic ion with a linear structure, which possesses chemical properties similar to halide ions . In inorganic and organic industries, thiocyanate has been used as chemical raw materials for manufacturing thiourea , cyanide and ferrocyanide , as well as efficient catalyst for polymerization of organic compounds . Moreover, thiocyanate has been wildly employed in recovery of noble metals in metallurgy .…”
Section: Introductionmentioning
confidence: 99%